Sensitivity of model-generated daytime surface heat fluxes over snow to land-cover changes - Strack, John E., author (Colorado State University. Libraries, 2001)
Snow cover can significantly suppress daytime temperatures by increasing the surface albedo and limiting the surface temperature to 0°C. The strength of this effect is dependent upon how well the snow can cover, or mask, the underlying surface. In regions where tall vegetation protrudes through a shallow layer of snow the temperature-reducing effects of the snow will be suppressed since the protruding vegetation will absorb solar radiation and emit an upward turbulent heat flux. This means that an atmospheric model must have a reasonable representation of the land cover, as well as be able to correctly prognose snow depth, if an accurate simulation of surface heat fluxes, air temperatures, and boundary layer structure is to be made. If too much vegetation protrudes through the snow then the surface sensible heat flux will be too large and the air temperatures will be too high. In this study four simulations are run with RAMS 4.30 for a snow event that occurred in 1988 over the Texas Panhandle. The first simulation, called the control, is run with the most realistic version of the current land cover and the results verified against both ground stations and aircraft data. Simulations 2 and 3 use the default methods of specifying land cover in RAMS 4.29 and RAMS 4.30 respectively. The significance of these variations in land-cover definition are then examined by comparing with the control run. Finally, the last simulation is run with the land cover defined as all short grass, the natural cover for the region. The results of this study indicate that variations in the land-cover specification can lead to differences in sensible heat flux over snow as large as 80 W m-2 . These differences in sensible heat flux can then lead to differences in daytime temperatures by as much as 6°C. Also, the height of the afternoon boundary layer can vary as much as 200-300 m. In addition, the results suggest that daytime temperatures are cooler over snow in the regions where short grass has been converted to cropland while they appear to be warmer over regions where shrubs have increased.
Fall 2001.
Also issued as author's thesis (M.S.) -- Colorado State University, 2001.
Keywords: Plant-snow relationship